UJI SUN PROTECTION FACTOR (SPF) DAN AKTIVITAS PEREDAMAN RADIKAL BEBAS PADA EKSTRAK TEMU PUTIH (Curcuma zedoaria) - Dewi, Aptika Oktaviana; Rikumahu, Laurentcia Filliks; Azzahratunnisa, Rifa Pasha; Khotimah, Prima Khusnul; Aprilia, Intan; Rosydah, Ismah (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
White turmeric (Curcuma zedoaria. Rosc) is a medicinal plant that belongs to the Zingiberaceae family and is part of the Curcuma genus. The rhizome of white temu contains more than 10 sesquiterpenes, such as curcumin, ethyl p-methoxycinnamate, β-turmerone, and others. The extract of temu lawak contains flavonoids, terpenoids, saponins, and alkaloids. White temu has potential as an antioxidant and sunscreen, but it is still seldom optimally utilized. This study aims to evaluate the Sun Protector Factor (SPF) value and the ability of white turmeric extract (Curcuma zedoaria. Rosc) to scavenge free radicals. The extraction was performed by maceration using 70% ethanol as a solvent at a ratio of 1:10. Phytochemical screening results indicate the presence of alkaloids, flavonoids, phenolics, and phytosterols in the extract. The SPF test was conducted in vitro using a UV-Vis spectrophotometer through the Mansur method, obtaining an SPF value of 16.17 at a concentration of 500 ppm and 30.98 at a concentration of 1000 ppm, which falls into the ultra protection category. The antioxidant activity test was conducted using the DPPH method at a maximum wavelength of 515 nm, with the highest percentage inhibition reaching 80% at a concentration of 500 ppm. The obtained IC50 value is 93.43 ppm. These results indicate that white temu extract has potential for development as an active ingredient in natural sunscreen and also as an antioxidant.